Tüm Yönleriyle Dil ve Konuşma Bozukluklarında Değerlendirme - Sezgin, M. Emre; Yılmaz, Ayşegül; Arslan, Berkay; Ayas, Harun; Berber Çiftci, Hilal; Barmak, Elife; Atabay İleri, Özden; Atila Çağlar, Nazmiye; Çıldır, Bünyamin; Kara, İlkem; Altınsoy, Aslı; Karalı, Fenise Selin; et al. (2023)
-